Transactional Memory. - LARUS, JAMES; KOZYRAKIS, CHRISTOS (Communications of the ACM, 2008)
The article discusses transactional memory (TM), examining its use in parallel programing. The challenge of parallel programing are the same as sequential programming, but also includes the difficulty of interaction coordination among tasks that are executing concurrently, the article indicates. Topics include the historic transition from sequential to parallel computation, and finding abstractions for expressing parallel computation. Also discussed is the use of TM as a programming construct which offers high-level abstraction for writing parallel programs.